Embracing the PhD journey: From odyssey to jewels - Zuraina, Ali (Penerbit UMPSA, 2024)
For academicians, pursuing a PhD is something that cannot be escaped as they need to obtain the degree to teach at the tertiary level education. For me, I realised the fact that I need to do a PhD when having to work at one of the universities in the East Coast of Malaysia. I have never thought of becoming a lecturer and teaching at a university. Having worked for almost a year in the capital city of Malaysia; clocking in when the sun is rising and clocking out when the moon is ticking, I realised that I do not want to work in that condition for a long time. It seemed that my day was only for working and I went home just for sleeping. The next day I woke up again doing the same routine; I felt that this work hectic was just not worth it. I knew that it was only for a temporary period, since I just graduated with my bachelor's degree.